Dietary Fat and Prostate Cancer Relationship Using Trimmed Regression Under Uncertainty - Aslam, Muhammad; AL-Marshadi, Ali Hussein (Frontiers in Nutrition, 2022)
In this paper, a new trimmed regression model under the neutrosophic is introduced. The mathematical model of the new regression model along with its neutrosophic form is given. The methods to find the error sum of square and trended values are also given. The trimmed neutrosophic correlation is also introduced in the paper. The proposed trimmed regression is applied to prostate cancer. From the analysis, it is concluded that the proposed model provides the minimum error sum of square as compared to the existing regression model under neutrosophic statistics. It is found that the proposed model is quite effective to forecast prostate cancer patients under an indeterminacy setting.